The new international law : an anthology - Eriksen, Christoffer C.; Emberland, Marius, 1970- (Raoul Wallenberg Institute human rights library ;, 2010)
This volume contains revised versions of a select number of research papers presented at a conference in Oslo, Norway, entitled "The New International Law". The conference was subtitled "Polycentric Decision-making Structures and Fragmented Spheres of Law: What Implications for the New Generation of International Legal Discourse?" This subtitle signals the most important elements of the conference's main purpose which was to be a project in line with certain strands of contemporary scholarship on international law; scholarship that bases itself on certain assumptions regarding what are importan.